Microstructural properties and wear resistance of Fe-Cr-Co-Ni-Mo-based high entropy alloy coatings deposited with different coating techniques - Oppong, Gifty B.; Geambazu, Laura E.; Ormsdottir, Arna M.; Gunnarsson, Baldur G.; Csaki, Ioana; Fanicchia, Francesco; Kovalov, Danyil; Karlsdóttir, Sigrún N. (MDPI, 2022)
Materials can be subjected to severe wear and corrosion due to high temperature, high pressure and mechanical loads when used in components for the production of geothermal power. In an effort to increase the lifetime of these components and thus decrease cost due to maintenance High-Entropy Alloy Coatings (HEACs) were developed with different coating techniques for anti-wear properties. The microstructure, mechanical and tribological properties of CoCrFeNiMox (at% x = 20, 27) HEACs deposited by three different technologies—high-velocity oxygen fuel (HVOF), laser cladding (LC) and electro-spark deposition (ESD)—are presented in this study. The relationship between surface morphology and microstructural properties of the as-deposited coatings and their friction and wear behavior is assessed to evaluate their candidacy as coatings for the geothermal environment. The wear rates were lower for the HVOF coatings compared to LC and ESD-produced coatings. Similarly, a higher hardness (445 ± 51 HV) was observed for the HVOF HEACs. The mixed FCC, BCC structure and the extent of σ + µ nano precipitates are considered responsible for the increased hardness and improved tribological performance of the HEACs. The findings from the study are valuable for the development of wear-resistant HEAC for geothermal energy industry applications where high wear is encountered.
Keywords: spark deposition; cladding; thermal spraying; high-entropy alloy; dry sliding wear